Effect of metals compatibility on fluorine-doped tin oxide catalyst for glycerol conversion to 1,2-Propanediol - Samad, Wan Zurina; Wan Isahak, Wan Nor Roslam; Hamzah, Noraini; Yarmo, Mohd Ambar; Yusop, Muhammad Rahimi (Trans Tech. Publications, 2017)
The effect of metals on support material fluorine-doped tin oxide (FTO), were studied. A series of metals such as ruthenium (Ru), osmium (Os), palladium (Pd), and copper (Cu) on FTO support were prepared by a simple wet mixture method, and attempted as a heterogeneous catalyst to enhance the hydrogenolysis of glycerol converted to 1,2-propanediol (1,2-PDO). The physicochemical properties of the catalysts were characterized by XRD, XPS, BET, FESEM, TEM, TPR, and TPD techniques. In particular, the catalyst of Ru-FTO was recorded as a good catalyst with an optimum glycerol conversion of 100% and 1,2-PDO selectivity of 94% respectively. It was suggesting that the acid an basic properties of the catalyst could achieved the C-O and C-H bond dissociation by formation of different intermediates of acetol and acetaldehyde to become 1,2-PDO. Despite that, some reaction parameters were evaluated and optimized reaction condition were established